Modern pharmacotherapy of psoriatic arthritis - Yu. L. Korsakova; T. V. Korotaeva (Научно-практическая ревматология)
The lecture presents the modern principles of treatment of psoriatic arthritis (PSA), taking into account the heterogeneity of the manifestations of this disease and the presence of comorbid conditions, information on the effectiveness and tolerability of drugs that are used in the Russian Federation in PSA.